Practical heat pump and storage integration into non-continuous processes: A hybrid approach utilizing insight based and nonlinear programming techniques. (1st September 2019) - Stampfli, Jan A.; Atkins, Martin J.; Olsen, Donald G.; Walmsley, Michael R.W.; Wellig, Beat
Abstract: This paper focuses on industrial heat pump (HP) integration in non-continuous processes. To achieve the necessary time-wise process decoupling of the HP system, heat recovery loops (HRLs) with stratified storages are used. This design type can be modeled as a mixed integer nonlinear programming problem which often results in expensive mathematical formulations. The challenge is addressed by a practical method that combines the insight based approach of Pinch Analysis with mathematical programming techniques to give the engineer more flexibility for the application of the method and to avoid long computation times. By the use of the insight based methods, the solution space of the mathematical formulation is restricted, and thus its complexity is reduced to a nonlinear programming problem optimizing the temperature levels in the HP-HRL system. As an objective, total annual costs (TAC) of the HP-HRL system are minimized. The developed hybrid method is applied to a dairy site and compared in terms of approach temperatures, temperature lift of the HP, TAC, and greenhouse gas emissions to the existing methods. It is shown, that the hybrid method provides realistic approach temperatures in contrast to the existing insight based method. Graphical abstract: Image 1 Highlights: A hybrid approach for heat pump integration in non-continuous processes. Insight based techniques to ensure practicality and applicability of the method. Nonlinear optimization for an optimal solution within the restricted solution space. Utilizing heat recovery loops for time-wise process decoupling of the heat pump.